2002
DOI: 10.1111/j.1095-8649.2002.tb01762.x
|View full text |Cite
|
Sign up to set email alerts
|

Fish and fisheries of the tidal Thames: management of the modern resource, research aims and future pressures

Abstract: In recent decades, following the cleanup in the 1960s, the Thames Estuary has become a major nursery ground for economic and conservation species, and has seen the development of substantial commercial and recreational fisheries. The Environment Agency has both sea fisheries and freshwater fisheries statutory powers in the estuary. A unique and focussed survey programme has been developed to inform management policies. A Fisheries Management Action Plan has been developed to promote integrated salmonid, eel An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Implementation of the EU Water Framework Directive, the Nitrates Directive and the Urban Wastewater Directives should be conducive to the improvement of water quality in Irish rivers and estuaries, which could, in turn, be conducive to shad conservation in the four Irish SACs. Improved water quality has led to the upstream displacement of the major shad spawning areas in the R. Elbe (Thiel et al, 1996) and contributed to the re-appearance of shad in the Thames (Colclough et al, 2002) and the Clyde (Maitland & Lyle, 2001). While none of the four current Irish SACs is designated for Allis shad, it is likely that, if Twaite shad reach a satisfactory conservation status within these waters then the water quality and habitat conditions would be conducive for Allis shad to attain a similar status.…”
Section: Stagementioning
confidence: 98%
“…Implementation of the EU Water Framework Directive, the Nitrates Directive and the Urban Wastewater Directives should be conducive to the improvement of water quality in Irish rivers and estuaries, which could, in turn, be conducive to shad conservation in the four Irish SACs. Improved water quality has led to the upstream displacement of the major shad spawning areas in the R. Elbe (Thiel et al, 1996) and contributed to the re-appearance of shad in the Thames (Colclough et al, 2002) and the Clyde (Maitland & Lyle, 2001). While none of the four current Irish SACs is designated for Allis shad, it is likely that, if Twaite shad reach a satisfactory conservation status within these waters then the water quality and habitat conditions would be conducive for Allis shad to attain a similar status.…”
Section: Stagementioning
confidence: 98%
“…Witkowski, 1992;Birstein, 1993;Thiel et al, 1995;Peter, 1998;Boyer et al, 2000;Bianco and Ketmaier, 2001;Raat, 2001;Colclough et al, 2002;de Groot, 2002;Vasil'eva,In addition to fishing pressure, river lampreys within the Humber basin are subject to other potentially detrimental influences, including periods of poor water quality during low flows in the tidal Ouse and the presence of numerous barriers, which may reduce longitudinal connectivity within the system (Lucas and Baras, 2001). The aim of this study, therefore, was to investigate the pattern of relative abundance and exploitation of adult river lampreys in the tidal Ouse to help meet the conservation objectives for river lampreys in this river and more generally.…”
Section: Introductionmentioning
confidence: 98%
“…Thus, on the basis of P. marinus catches from fisheries, Beaulaton et al (2008) suggested a progressive population increase of P. marinus in the rivers Adour, Garonne, Vilaine and Rhine, between 1990 and 2005. Signs of a possible improvement of P. marinus populations in the UK have been observed; one of the factors responsible for this recovery is considered to be the restoration of water quality (Colclough et al 2002;Joint Nature Conservation Committee 2007). Also, Pereira et al (2012) mentioned a recent rise in the occurrence of this species in coastal areas and rivers of Iceland.…”
Section: Discussionmentioning
confidence: 98%